Editorial [to] Themed issue on sustainability in energy and buildings, part 1 - Calautit, John Kaiser (Institution of Civil Engineers, 2017)
This themed issue includes the selected papers from the proceedings of the seventh International Conference on Sustainability and Energy in Buildings 2015 (SEB15), which was successfully held in the vibrant city of Lisbon, Portugal and was organised by the Universidade Nova de Lisbon (New University of Lisbon) in partnership with KES International. Annually, the conference brings together researchers and government and industry professionals to discuss the future of energy in buildings, neighbourhoods and cities from a theoretical, practical, implementation and simulation perspective.